Dividing the Spoils : Pensions, Privatization, and Reform in Russia's Transition - Kapstein, Ethan B. (World Bank, Washington, DC, 2015)
The authors present a political economy model in which policy is the outcome of an interaction between three actors: government (G), managers and workers (W), and transfer recipients (P). The government's objective is to stay in power, for which it needs the support of either P or W. It can choose slow privatization with little asset stripping and significant taxation, thus protecting the fiscal base out of which it pays pensioners relatively well (as in Poland). Or it can give away assets and tax exemptions to managers and workers, who then bankroll it and deliver the vote, but it thereby loses taxes and pays little to pensioners (as in Russia). The authors apply this model to Russia for the period 1992-96. An empirical analysis of electoral behavior in the 1996 presidential election shows that the likelihood of someone voting for Yeltsin did not depend on that person's socioeconomic group per se. Those who tended to vote for Yeltsin were richer, younger, and better educated and had more favorable expectations for the future. Entrepreneurs, who had more of these characteristics, tended to vote for Yeltsin as a result, while pensioners, who had almost none, tended to vote against Yeltsin. Unlike Poland, Russia failed to create pluralist politics in the early years of the transition, so no effective counterbalance emerged to offset managerial rent-seeking and the state was easily captured by well-organized industrial interests. The political elite were reelected because industrial interests bankrolled their campaign in return for promises that government largesse would continue to flow. Russia shows vividly how political economy affects policymaking, because of how openly and flagrantly government granted favors in return for electoral support. Bur special interests, venal bureaucrats, and the exchange of favors tend to be the rule, not the exemption, elsewhere as well.